2019
DOI: 10.26656/fr.2017.4(3).305
|View full text |Cite
|
Sign up to set email alerts
|

Variety difference of physicochemical and cooking properties of selected brown rice from Thailand and Malaysia

Abstract: Rice is a major staple food in Thailand and Malaysia. Although brown rice is a highly healthy substitute, preference is very low due to its texture and cooking quality. However, there are some brown rice varieties such as Sungyod (SY), Chiang (CH), Lepnok (LP) from Thailand and long grain specialty 1(LS 1 ) and long grain specialty 2 (LS 2 ) from Malaysian peninsula are commonly consumed in such areas. This study aimed to investigate the physicochemical and the cooking properties of these brown rice to underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The difference in variety in rice grains' hardness is due to the difference in the compact arrangement between rice cultivars of starch granules. The Thai variety may be hard due to its higher content of the bran layer, while lower hardness in Malaysian rice is assumed due to the thin bran layer's likely presence (Chapagai et al, 2020). Besides, the lower hardness level is preferred as it will affect the cooking properties.…”
Section: Physical Properties Of Malaysian Rice and Thai Ricementioning
confidence: 99%
See 1 more Smart Citation
“…The difference in variety in rice grains' hardness is due to the difference in the compact arrangement between rice cultivars of starch granules. The Thai variety may be hard due to its higher content of the bran layer, while lower hardness in Malaysian rice is assumed due to the thin bran layer's likely presence (Chapagai et al, 2020). Besides, the lower hardness level is preferred as it will affect the cooking properties.…”
Section: Physical Properties Of Malaysian Rice and Thai Ricementioning
confidence: 99%
“…The awareness of physicochemical characteristics of the selected rice (Malaysian & Thai rice) is essentially vital during harvesting crops, transporting and dimensioning the storage process, manufacturing and operating various equipment applied in the main postharvest processing operation (Ghadge & Prasad, 2012). Previously, research was performed on various brown rice and white rice (Chapagai et al, 2020;Sam Lum, 2017). Meanwhile, Thomas et al (2013) reported differences in various brown rice from Thailand and Malaysia.…”
Section: Introductionmentioning
confidence: 99%
“…It also might be caused by the physiological activities of the mineral, possibly due to the respiration process that subsequently decreases the mineral content in the rice samples (Nur Shafinaz et al 2022). However, some minerals can be volatilized or reduced when heated at high temperatures during the drying process, particularly vitamins B and C (Chapagai et al 2020). This study shows that the storage temperatures indirectly promote the physiological process and affect the ash content of rice samples.…”
Section: Resultsmentioning
confidence: 81%
“…These results showed that the WR had a relatively higher moisture content than the BR in preparation methods 1 and 3. Since the BR has a high-fibre bran, more water is needed to cook BR, and it is demonstrated that the bran layer inhibits moisture absorption (Chapagai et al 2020). Plus, it may be due to the drying effects of the exothermic reaction of the dehusking procedure (Kim & Lee 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Brown rice is less popular than milled or white rice, despite being higher in lipids, proteins, and vitamins B1 and B2 (Cho and Lim, 2016). It also has certain drawbacks, such as a longer cooking time and a harder cooked texture due to the bran's fiber content (Heinemann et al, 2005;Patil and Khan, 2011;Chapagai et al, 2017;Mohan et al, 2017). The oil content in the bran reduces its shelf life due to rancidity (Parnsakhorn and Langkapin, 2013).…”
Section: Introductionmentioning
confidence: 99%